A lithium iron phosphate positive electrode material and preparation method thereof

By undergoing plasma treatment, ball grinding and thermal homogenization on the lithium iron phosphate positive electrode material, the capacity stability of existing materials under high magnification and high temperature conditions is solved, and the efficiency of the material is significantly improved.

CN119176536BActive Publication Date: 2025-03-04GANZHOU CYCLEWELL TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411686786.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-04
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The existing lithium iron phosphate positive electrode materials have deteriorated discharge specific capacity stability and capacity retention rate under high magnification conditions, especially under high temperature and multiple cycle conditions, which limits the efficiency of the product.

Method used

By treating the precursor lithium iron phosphate in a plasma box, then co-mixed with the first ball mill and the second ball mill, and performing thermal homogenization treatment, the activity performance and structural stability of the lithium iron phosphate body are optimized.

Benefits of technology

The discharge specific capacity stability and capacity retention rate of lithium iron phosphate positive electrode material under high magnification conditions are significantly improved, especially under high temperature and multiple cycle conditions, the capacity stability of the product is significant.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention relates to the technical field of positive electrode materials, and in particular to a lithium iron phosphate positive electrode material and a preparation method thereof, comprising the following steps: treating a precursor lithium iron phosphate in a plasma box, with a treatment power of 400-450W and a treatment time of 10-20min, and completing the treatment to obtain a treated lithium iron phosphate body; mixing the treated lithium iron phosphate body and a first ball milling liquid in a weight ratio of (5-7):2, and completing the ball milling to obtain a first ball-milled lithium iron phosphate body. The lithium iron phosphate positive electrode material of the present invention uses a precursor lithium iron phosphate to be first treated with plasma to optimize the activity efficiency of the lithium iron phosphate body, and then improves the coordination of the first ball milling liquid and the second ball milling liquid, and then reconciles the thermal homogenization synergy, so that the obtained positive electrode material has excellent discharge specific capacity stability under high rate conditions, and a significant capacity retention rate, and a significant capacity stability effect of the product under high temperature and multiple cycle conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of positive electrode materials, and in particular to a lithium iron phosphate positive electrode material and a preparation method thereof. Background Art

[0002] Lithium iron phosphate cathode material is a lithium battery material widely used in pure electric vehicles. The phosphorus-oxygen bond in the crystal of this material is stable and very difficult to decompose. Therefore, it will not collapse and generate heat like lithium cobalt oxide when it is exposed to high temperature or overcharge, and has better safety.

[0003] Under high-rate conditions, the discharge specific capacity stability and capacity retention rate of existing positive electrode materials deteriorate, limiting the use efficiency of the product. Under high temperature and multiple cycle conditions, the capacity stability of the product deteriorates, further limiting the use efficiency of the product. Summary of the invention

[0004] In view of the defects of the prior art, the object of the present invention is to provide a lithium iron phosphate positive electrode material and a preparation method thereof to solve the problems raised in the above background technology.

[0005] The present invention solves the technical problem by adopting the following technical solution:

[0006] The present invention provides a method for preparing a lithium iron phosphate positive electrode material, comprising the following steps:

[0007] Step 1: The precursor lithium iron phosphate is first treated in a plasma box, the treatment power is 400-450W, the treatment time is 10-20min, and the treatment is completed to obtain a treated lithium iron phosphate body;

[0008] Step 2: Mix the treated lithium iron phosphate body and the first ball milling solution in a weight ratio of (5-7):2, and then perform the first ball milling treatment. After the ball milling is completed, filter and dry to obtain the first ball milled lithium iron phosphate body;

[0009] Step 3: heat homogenizing the lithium iron phosphate obtained by the first ball milling, and obtaining heat homogenized lithium iron phosphate after the treatment is completed;

[0010] Step 4: Mix the heat-homogenized lithium iron phosphate and the second ball-milling liquid in a weight ratio of (5-7):2 and perform a second ball-milling treatment. After the ball-milling is completed, filter and dry to obtain a lithium iron phosphate positive electrode material.

[0011] Preferably, the first ball milling treatment is performed at a ball milling speed of 1000-1500 r / min and the ball milling time is 35-45 min;

[0012] The second ball milling treatment is performed at a ball milling speed of 650-750 r / min and the ball milling is performed for 1-2 hours.

[0013] Preferably, the specific operation steps of the heat homogenization treatment are:

[0014] S01: First heat treat at 300~320℃ for 10~15min, then heat to 550~600℃ at a rate of 2~5℃ / min, and keep warm for 1~2h;

[0015] S02: Heat to 1050°C at a rate of 4-7°C / min, keep warm for 50 min, and finally cool to room temperature at a rate of 1-3°C / min.

[0016] Preferably, the preparation method of the first ball milling liquid is:

[0017] S11: preheat the nano-alumina at 60-70°C for 10-15 minutes, and then prepare a 2-5% by mass cobalt nitrate solution and a 6% by mass sodium silicate solution;

[0018] S12: then 4-7 parts of preheated nano-alumina, 2-5 parts of cobalt nitrate solution, and 1-3 parts of silane coupling agent KH550 are mixed and added into 7-11 parts of sodium silicate solution, and stirred and mixed to obtain nano-alumina liquid;

[0019] S13: The nano-alumina liquid and the ball milling additive are mixed and stirred in a weight ratio of (5-7):3, and the stirring is completed to obtain a first ball milling liquid.

[0020] Preferably, the rotation speed of the blending and stirring process in S13 is 550-650 r / min, and the stirring time is 35-45 min.

[0021] Preferably, the preparation method of the ball milling additive is:

[0022] 3-5 parts of sodium metaborate and 2-5 parts of montmorillonite are added to 6-8 parts of dopamine hydrochloride solution, and then 1-3 parts of nano-silica sol are added and mixed to obtain a modified immersion solution;

[0023] The nano-lanthanum oxide powder is immersed in a sufficient amount of modified immersion liquid and stirred at a stirring speed of 550-650 r / min for 20-30 minutes. After the stirring is completed, the powder is filtered and dried to obtain a ball milling additive.

[0024] Preferably, the mass fraction of the dopamine hydrochloride solution is 3-5%.

[0025] Preferably, the second ball milling solution is prepared by:

[0026] S101: preparing a sodium dodecylbenzene sulfonate solution with a mass fraction of 2-5% and a chitosan solution with a mass fraction of 3-6%;

[0027] S102: 3-5 parts of carbon fiber, 1-3 parts of nano-silicon dioxide, 4-7 parts of sodium dodecylbenzene sulfonate solution and 2-4 parts of chitosan solution are fully mixed to obtain a second ball milling solution.

[0028] Preferably, the speed for sufficient blending is 550-750 r / min, and the blending time is 45-55 min.

[0029] The present invention also provides a lithium iron phosphate positive electrode material prepared by a method for preparing a lithium iron phosphate positive electrode material.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] 1. The lithium iron phosphate positive electrode material of the present invention adopts a precursor lithium iron phosphate which is first subjected to plasma treatment to optimize the activity efficiency of the lithium iron phosphate body, and then improved by co-mixing the first ball milling liquid and the second ball milling liquid, and then blended with thermal homogenization synergy, so that the obtained positive electrode material has excellent discharge specific capacity stability and significant capacity retention under high rate conditions, and the product has significant capacity stability under high temperature and multiple cycle conditions;

[0032] 2. The first ball milling liquid is improved by preheating nano-alumina, and then combined with cobalt nitrate solution, silane coupling agent KH550 and sodium silicate solution. Through the coordination between the raw materials, the nano-alumina can be more stably coordinated with the ball milling additive. The sodium metaborate, montmorillonite, dopamine hydrochloride solution and nano-silica sol in the ball milling additive are modified immersion liquids. The nano-lanthanum oxide powder is immersed in the modified immersion liquid and stirred. The first ball milling liquid and the precursor lithium iron phosphate are better matched and assisted by the coordination between the raw materials, thereby improving the performance of the product;

[0033] 3. The second ball-milling liquid uses carbon fiber and nano-silica as the matrix material, and is matched with sodium dodecylbenzene sulfonate solution and chitosan solution. Through the coordination between the raw materials, the carbon fiber and nano-silica reinforce the system structure, so that the second ball-milling liquid and the first ball-milling liquid can be better coordinated, and the precursor lithium iron phosphate is further improved. The temperature is heat treated at 300-320°C for 10-15min, and then the temperature is increased to 550-600°C at a rate of 2-5°C / min and kept warm for 1-2h; then the temperature is increased to 1050°C at a rate of 4-7°C / min, and the temperature is kept warm for 50min, and finally cooled to room temperature at a rate of 1-3°C / min. Through segmented thermal heating treatment and mild thermal improvement, the second ball-milling liquid and the first ball-milling liquid are coordinated, and the performance of the product is further improved. DETAILED DESCRIPTION

[0034] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] A method for preparing a lithium iron phosphate positive electrode material of this embodiment includes the following steps:

[0036] Step 1: The precursor lithium iron phosphate is first treated in a plasma box, the treatment power is 400-450W, the treatment time is 10-20min, and the treatment is completed to obtain a treated lithium iron phosphate body;

[0037] Step 2: Mix the treated lithium iron phosphate body and the first ball milling solution in a weight ratio of (5-7):2, and then perform the first ball milling treatment. After the ball milling is completed, filter and dry to obtain the first ball milled lithium iron phosphate body;

[0038] Step 3: heat homogenizing the lithium iron phosphate obtained by the first ball milling, and obtaining heat homogenized lithium iron phosphate after the treatment is completed;

[0039] Step 4: Mix the heat-homogenized lithium iron phosphate and the second ball-milling liquid in a weight ratio of (5-7):2 and perform a second ball-milling treatment. After the ball-milling is completed, filter and dry to obtain a lithium iron phosphate positive electrode material.

[0040] The first ball milling process of this embodiment has a ball milling speed of 1000-1500 r / min and a ball milling time of 35-45 min.

[0041] The second ball milling treatment is performed at a ball milling speed of 650-750 r / min and the ball milling is performed for 1-2 hours.

[0042] The specific operation steps of the heat homogenization treatment in this embodiment are:

[0043] S01: First heat treat at 300~320℃ for 10~15min, then heat to 550~600℃ at a rate of 2~5℃ / min, and keep warm for 1~2h;

[0044] S02: Heat to 1050°C at a rate of 4-7°C / min, keep warm for 50 min, and finally cool to room temperature at a rate of 1-3°C / min.

[0045] The preparation method of the first ball milling liquid of this embodiment is:

[0046] S11: preheat the nano-alumina at 60-70°C for 10-15 minutes, and then prepare a 2-5% by mass cobalt nitrate solution and a 6% by mass sodium silicate solution;

[0047] S12: then 4-7 parts of preheated nano-alumina, 2-5 parts of cobalt nitrate solution, and 1-3 parts of silane coupling agent KH550 are mixed and added into 7-11 parts of sodium silicate solution, and stirred and mixed to obtain nano-alumina liquid;

[0048] S13: The nano-alumina liquid and the ball milling additive are mixed and stirred in a weight ratio of (5-7):3, and the stirring is completed to obtain a first ball milling liquid.

[0049] In S13 of the present embodiment, the rotation speed of the blending and stirring process is 550-650 r / min, and the stirring time is 35-45 min.

[0050] The preparation method of the ball milling additive of this embodiment is:

[0051] 3-5 parts of sodium metaborate and 2-5 parts of montmorillonite are added to 6-8 parts of dopamine hydrochloride solution, and then 1-3 parts of nano-silica sol are added and mixed to obtain a modified immersion solution;

[0052] The nano-lanthanum oxide powder is immersed in a sufficient amount of modified immersion liquid and stirred at a stirring speed of 550-650 r / min for 20-30 minutes. After the stirring is completed, the powder is filtered and dried to obtain a ball milling additive.

[0053] The mass fraction of the dopamine hydrochloride solution in this embodiment is 3-5%.

[0054] The preparation method of the second ball milling liquid of this embodiment is:

[0055] S101: preparing a sodium dodecylbenzene sulfonate solution with a mass fraction of 2-5% and a chitosan solution with a mass fraction of 3-6%;

[0056] S102: 3-5 parts of carbon fiber, 1-3 parts of nano-silicon dioxide, 4-7 parts of sodium dodecylbenzene sulfonate solution and 2-4 parts of chitosan solution are fully mixed to obtain a second ball milling solution.

[0057] The rotation speed for sufficient blending in this embodiment is 550-750 r / min, and the blending time is 45-55 min.

[0058] The lithium iron phosphate positive electrode material is prepared by a method for preparing a lithium iron phosphate positive electrode material in this embodiment.

[0059] Example 1

[0060] A method for preparing a lithium iron phosphate positive electrode material of this embodiment includes the following steps:

[0061] Step 1: The precursor lithium iron phosphate is first treated in a plasma box, the treatment power is 400W, the treatment time is 10min, and the treatment is completed to obtain a treated lithium iron phosphate body;

[0062] Step 2: Mix the treated lithium iron phosphate body and the first ball milling liquid in a weight ratio of 5:2 and perform the first ball milling treatment. After the ball milling is completed, filter and dry to obtain the first ball milled lithium iron phosphate body;

[0063] Step 3: heat homogenizing the lithium iron phosphate obtained by the first ball milling, and obtaining heat homogenized lithium iron phosphate after the treatment is completed;

[0064] Step 4: Mix the heat-homogenized lithium iron phosphate and the second ball-milling liquid in a weight ratio of 5:2 and perform a second ball-milling treatment. After the ball-milling is completed, filter and dry to obtain a lithium iron phosphate positive electrode material.

[0065] The first ball milling process of this embodiment has a ball milling speed of 1000 r / min and a ball milling time of 35 min.

[0066] The second ball milling treatment was performed at a ball milling speed of 650 r / min and the ball milling was performed for 1 hour.

[0067] The specific operation steps of the heat homogenization treatment in this embodiment are:

[0068] S01: First heat treat at 300℃ for 10min, then heat up to 550℃ at a rate of 2℃ / min and keep at this temperature for 1h;

[0069] S02: Heat to 1050°C at a rate of 4°C / min, keep warm for 50 min, and finally cool to room temperature at a rate of 1°C / min.

[0070] The preparation method of the first ball milling liquid of this embodiment is:

[0071] S11: preheating the nano-alumina at 60°C for 10 minutes, and then preparing a 2% by mass cobalt nitrate solution and a 6% by mass sodium silicate solution;

[0072] S12: Then 4 parts of preheated nano-alumina, 2 parts of cobalt nitrate solution, and 1 part of silane coupling agent KH550 are mixed and added into 7 parts of sodium silicate solution, and stirred to mix well to obtain nano-alumina liquid;

[0073] S13: The nano-alumina liquid and the ball milling additive are mixed and stirred in a weight ratio of 5:3, and the stirring is completed to obtain a first ball milling liquid.

[0074] In S13 of the present embodiment, the rotation speed of the blending and stirring process is 550 r / min, and the stirring time is 35 min.

[0075] The preparation method of the ball milling additive of this embodiment is:

[0076] 3 parts of sodium metaborate and 2 parts of montmorillonite are added to 6 parts of dopamine hydrochloride solution, and then 1 part of nano silica sol is added and mixed thoroughly to obtain a modified immersion solution;

[0077] The nano-lanthanum oxide powder is immersed in a sufficient amount of the modified immersion liquid and stirred at a stirring speed of 550 r / min for 20 minutes. After the stirring is completed, the powder is filtered and dried to obtain a ball milling additive.

[0078] The mass fraction of the dopamine hydrochloride solution in this embodiment is 3%.

[0079] The preparation method of the second ball milling liquid of this embodiment is:

[0080] S101: preparing a 2% by mass sodium dodecylbenzene sulfonate solution and a 3% by mass chitosan solution;

[0081] S102: 3 parts of carbon fiber, 1 part of nano-silicon dioxide, 4 parts of sodium dodecylbenzene sulfonate solution and 2 parts of chitosan solution are fully blended to obtain a second ball-milling solution.

[0082] The rotation speed for sufficient blending in this embodiment is 550 r / min, and the blending time is 45 min.

[0083] The lithium iron phosphate positive electrode material is prepared by a method for preparing a lithium iron phosphate positive electrode material in this embodiment.

[0084] Example 2

[0085] A method for preparing a lithium iron phosphate positive electrode material of this embodiment includes the following steps:

[0086] Step 1: The precursor lithium iron phosphate is first treated in a plasma box, the treatment power is 450W, the treatment time is 20min, and the treatment is completed to obtain a treated lithium iron phosphate body;

[0087] Step 2: Mix the treated lithium iron phosphate body and the first ball milling liquid in a weight ratio of 7:2, and then perform the first ball milling treatment. After the ball milling is completed, filter and dry to obtain the first ball milled lithium iron phosphate body;

[0088] Step 3: heat homogenizing the lithium iron phosphate obtained by the first ball milling, and obtaining heat homogenized lithium iron phosphate after the treatment is completed;

[0089] Step 4: Mix the heat-homogenized lithium iron phosphate and the second ball-milling liquid in a weight ratio of 7:2 and perform a second ball-milling treatment. After the ball-milling is completed, filter and dry to obtain a lithium iron phosphate positive electrode material.

[0090] The first ball milling process of this embodiment has a ball milling speed of 1500 r / min and a ball milling time of 45 min.

[0091] The second ball milling treatment was performed at a ball milling speed of 750 r / min and the ball milling was performed for 2 h.

[0092] The specific operation steps of the heat homogenization treatment in this embodiment are:

[0093] S01: First heat treat at 320℃ for 15min, then heat up to 600℃ at a rate of 5℃ / min and keep at this temperature for 2h;

[0094] S02: Heat to 1050°C at a rate of 7°C / min, keep warm for 50 min, and finally cool to room temperature at a rate of 3°C / min.

[0095] The preparation method of the first ball milling liquid of this embodiment is:

[0096] S11: preheating the nano-alumina at 70°C for 15 minutes, and then preparing a 5% by mass cobalt nitrate solution and a 6% by mass sodium silicate solution;

[0097] S12: then 7 parts of preheated nano-alumina, 5 parts of cobalt nitrate solution, and 3 parts of silane coupling agent KH550 are mixed and added into 11 parts of sodium silicate solution, and stirred and mixed to obtain nano-alumina liquid;

[0098] S13: The nano-alumina liquid and the ball milling additive are mixed and stirred in a weight ratio of 7:3, and the stirring is completed to obtain a first ball milling liquid.

[0099] In S13 of the present embodiment, the rotation speed of the blending and stirring process is 650 r / min, and the stirring time is 45 min.

[0100] The preparation method of the ball milling additive of this embodiment is:

[0101] Add 5 parts of sodium metaborate and 5 parts of montmorillonite to 8 parts of dopamine hydrochloride solution, then add 3 parts of nano silica sol, and mix thoroughly to obtain a modified immersion solution;

[0102] The nano-lanthanum oxide powder is immersed in a sufficient amount of the modified immersion liquid and stirred at a stirring speed of 650 r / min for 30 minutes. After the stirring is completed, the powder is filtered and dried to obtain a ball milling additive.

[0103] The mass fraction of the dopamine hydrochloride solution in this embodiment is 5%.

[0104] The preparation method of the second ball milling liquid of this embodiment is:

[0105] S101: preparing a 5% by mass sodium dodecylbenzene sulfonate solution and a 6% by mass chitosan solution;

[0106] S102: 5 parts of carbon fiber, 3 parts of nano-silicon dioxide, 7 parts of sodium dodecylbenzene sulfonate solution and 4 parts of chitosan solution are fully blended to obtain a second ball-milling solution.

[0107] The rotation speed for sufficient blending in this embodiment is 750 r / min, and the blending time is 55 min.

[0108] The lithium iron phosphate positive electrode material is prepared by a method for preparing a lithium iron phosphate positive electrode material in this embodiment.

[0109] Example 3

[0110] A method for preparing a lithium iron phosphate positive electrode material of this embodiment includes the following steps:

[0111] Step 1: The precursor lithium iron phosphate is first treated in a plasma box, the treatment power is 420W, the treatment time is 15min, and the treatment is completed to obtain a treated lithium iron phosphate body;

[0112] Step 2: Mix the treated lithium iron phosphate body and the first ball milling liquid in a weight ratio of 3:1 and perform the first ball milling treatment. After the ball milling is completed, filter and dry to obtain the first ball milled lithium iron phosphate body;

[0113] Step 3: heat homogenizing the lithium iron phosphate obtained by the first ball milling, and obtaining heat homogenized lithium iron phosphate after the treatment is completed;

[0114] Step 4: Mix the heat-homogenized lithium iron phosphate and the second ball-milling liquid in a weight ratio of 3:1 and perform a second ball-milling treatment. After the ball-milling is completed, filter and dry to obtain a lithium iron phosphate positive electrode material.

[0115] The first ball milling process of this embodiment has a ball milling speed of 1250 r / min and a ball milling time of 40 min.

[0116] The second ball milling treatment was performed at a ball milling speed of 700 r / min and the ball milling was performed for 1.5 h.

[0117] The specific operation steps of the heat homogenization treatment in this embodiment are:

[0118] S01: first heat treatment at 310℃ for 12.5min, then heating to 575℃ at a rate of 3.5℃ / min and keeping at this temperature for 1.5h;

[0119] S02: Heat to 1050°C at a rate of 5.5°C / min, keep warm for 50 min, and finally cool to room temperature at a rate of 2°C / min.

[0120] The preparation method of the first ball milling liquid of this embodiment is:

[0121] S11: preheating the nano-alumina at 65°C for 12.5 minutes, and then preparing a 3.5% by mass cobalt nitrate solution and a 6% by mass sodium silicate solution;

[0122] S12: then 5.5 parts of preheated nano-alumina, 3.5 parts of cobalt nitrate solution, and 2 parts of silane coupling agent KH550 are mixed and added into 8.5 parts of sodium silicate solution, and stirred to mix well to obtain nano-alumina liquid;

[0123] S13: The nano-alumina liquid and the ball milling additive are mixed and stirred at a weight ratio of 2:1, and the stirring is completed to obtain a first ball milling liquid.

[0124] In S13 of the present embodiment, the rotation speed of the blending and stirring process is 600 r / min, and the stirring time is 40 min.

[0125] The preparation method of the ball milling additive of this embodiment is:

[0126] 4 parts of sodium metaborate and 3.5 parts of montmorillonite are added to 7 parts of dopamine hydrochloride solution, and then 2 parts of nano-silica sol are added and mixed thoroughly to obtain a modified immersion solution;

[0127] The nano-lanthanum oxide powder is immersed in a sufficient amount of the modified immersion liquid and stirred at a stirring speed of 600 r / min for 25 minutes. After the stirring is completed, the powder is filtered and dried to obtain a ball milling additive.

[0128] The mass fraction of the dopamine hydrochloride solution in this embodiment is 4%.

[0129] The preparation method of the second ball milling liquid of this embodiment is:

[0130] S101: preparing a 3.5% by mass sodium dodecylbenzene sulfonate solution and a 4.5% by mass chitosan solution;

[0131] S102: 4 parts of carbon fiber, 2 parts of nano-silicon dioxide, 5.5 parts of sodium dodecylbenzene sulfonate solution and 3 parts of chitosan solution are fully blended to obtain a second ball-milling solution.

[0132] The rotation speed for sufficient blending in this embodiment is 600 r / min, and the blending time is 50 min.

[0133] The lithium iron phosphate positive electrode material is prepared by a method for preparing a lithium iron phosphate positive electrode material in this embodiment.

[0134] Comparative Example 1

[0135] The difference from Example 3 is that the first ball milling liquid treatment is not used.

[0136] Comparative Example 2

[0137] The difference from Example 3 is that no nano-alumina liquid is added in the preparation of the first ball milling liquid.

[0138] Comparative Example 3

[0139] The difference from Example 3 is that no cobalt nitrate solution or silane coupling agent KH550 is added to the nano-alumina liquid.

[0140] Comparative Example 4

[0141] The difference from Example 3 is that preheated nano-alumina is not added to the nano-alumina liquid, and deionized water is used instead of the sodium silicate solution.

[0142] Comparative Example 5

[0143] The difference from Example 3 is that no ball milling additive is added in the preparation of the first ball milling solution.

[0144] Comparative Example 6

[0145] The difference from Example 3 is that the second ball milling liquid treatment is not used.

[0146] Comparative Example 7

[0147] The difference from Example 3 is that no carbon fiber and sodium dodecylbenzene sulfonate solution are added to the second ball milling liquid.

[0148] Comparative Example 8

[0149] The difference from Example 3 is that no nano-silicon dioxide and chitosan solution are added to the second ball milling solution.

[0150] Comparative Example 9

[0151] The difference from Example 3 is that no heat homogenization treatment is used.

[0152] Comparative Example 10

[0153] The difference from Example 3 is that the operation method of the heat homogenization treatment is different. First, the heat treatment is carried out at a temperature of 310°C for 12.5 minutes, and then the temperature is increased to 1050°C at a rate of 5.5°C / min, and the temperature is kept for 50 minutes, and then air-cooled to room temperature.

[0154] The performance of the products of Examples 1 to 3 and Comparative Examples 1 to 10 was tested, and the test results are as follows

[0155]

[0156] It can be seen from the tests of Comparative Examples 1-10 and Examples 1-3 that;

[0157] The product of Example 3 has excellent discharge specific capacity stability. The product still has excellent discharge specific capacity under 5C conditions. At the same time, the product has been cycled for 500 and 800 times under high temperature conditions of 5C and 65°C, and the capacity retention rate stability of the product is remarkable.

[0158] It can be seen from Comparative Examples 1, 6, 9 and Example 3 that the product performance stability deteriorates significantly when the first ball milling solution and the second ball milling solution are not used in the product, and the performance of the product also deteriorates when the heat homogenization treatment is not used. The product performance effect is most significant when the three are mixed.

[0159] It can be seen from Comparative Examples 1-5 and Example 3 that the performance of the products showed a trend of varying degrees of deterioration when no nano-alumina liquid was added to the first ball-milling liquid, no cobalt nitrate solution and silane coupling agent KH550 were added to the nano-alumina liquid, no preheated nano-alumina was added to the nano-alumina liquid, and the sodium silicate solution was replaced by deionized water, and no ball-milling additive was added to the first ball-milling liquid. At the same time, the performance of the product showed a more obvious deterioration when no ball-milling additive was added to the first ball-milling liquid. The performance of the nano-alumina liquid obtained by different methods showed a trend of deterioration. Only the first ball-milling liquid prepared by the nano-alumina liquid obtained by the specific method of the present invention and the ball-milling additive had the most significant product performance effect. The effects of other methods were not as obvious as those of the present invention.

[0160] It can be seen from Comparative Examples 7-8, Comparative Example 10 and Example 3 that the performance of the product also shows a trend of deterioration when carbon fiber and sodium dodecylbenzene sulfonate solution are not added to the second ball-milling liquid, and nano-silicon dioxide and chitosan solution are not added to the second ball-milling liquid. The second ball-milling liquid obtained by the method of the present invention has the most significant product performance effect, and the product performance also shows a trend of deterioration when heat homogenization treatment is obtained by different methods.

[0161] The present invention further explores the product performance through the preparation of ball milling additives;

[0162] Experimental Example 1

[0163] The only difference from Example 3 is that the modified immersion liquid treatment was not used in the preparation of the ball mill additive.

[0164] Experimental Example 2

[0165] The only difference from Example 3 is that no sodium metaborate is added to the modified immersion solution.

[0166] Experimental Example 3

[0167] The only difference from Example 3 is that no montmorillonite is added to the modified immersion solution.

[0168] Experimental Example 4

[0169] The only difference from Example 3 is that no nano-silica sol is added to the modified immersion solution and deionized water is used instead of the dopamine hydrochloride solution.

[0170] Experimental Example 5

[0171] The only difference from Example 3 is that no nano lanthanum oxide powder is added in the preparation of the ball milling additive.

[0172] Experimental Example 1-5 Product performance test, its performance is as follows;

[0173]

[0174] It can be seen from Experimental Examples 1-5 that the performance of the product changes when no modified immersion liquid treatment is used and no nano-lanthanum oxide powder is added in the preparation of the ball milling additive. Among the factors for preparing the ball milling additive, the performance deteriorates more significantly. In addition, when no sodium metaborate is added to the modified immersion liquid, no montmorillonite is added to the modified immersion liquid, no nano-silica sol is added to the modified immersion liquid, and deionized water is used instead of the dopamine hydrochloride solution, the performance of the product tends to deteriorate. The preparation compositions of the modified immersion liquid replaced by other methods are not as significant as the effect of the present invention. The ball milling additive obtained by using the specific modified immersion liquid of the present invention in combination with nano-lanthanum oxide powder has the most significant product performance effect. The effects of other methods are not as significant as the effect of the present invention.

[0175] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0176] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing a lithium iron phosphate positive electrode material, characterized in that: The following steps are involved: Step 1: The precursor lithium iron phosphate is first treated in a plasma box, the treatment power is 400-450W, the treatment time is 10-20min, and the treatment is completed to obtain a treated lithium iron phosphate body; Step 2: Mix the treated lithium iron phosphate body and the first ball milling solution in a weight ratio of (5-7):2, and then perform the first ball milling treatment. After the ball milling is completed, filter and dry to obtain the first ball milled lithium iron phosphate body; Step 3: heat homogenizing the lithium iron phosphate obtained by the first ball milling, and obtaining heat homogenized lithium iron phosphate after the treatment is completed; Step 4: Mix the heat-homogenized lithium iron phosphate and the second ball-milling liquid in a weight ratio of (5-7):2, and then perform a second ball-milling treatment. After the ball-milling is completed, the mixture is filtered and dried to obtain a lithium iron phosphate positive electrode material. The specific operation steps of the heat homogenization treatment are: S01: First heat treat at 300~320℃ for 10~15min, then heat to 550~600℃ at a rate of 2~5℃ / min, and keep warm for 1~2h; S02: Heat to 1050°C at a rate of 4-7°C / min, keep warm for 50 min, and finally cool to room temperature at a rate of 1-3°C / min; The preparation method of the first ball milling liquid is: S11: preheat the nano-alumina at 60-70°C for 10-15 minutes, and then prepare a 2-5% by mass cobalt nitrate solution and a 6% by mass sodium silicate solution; S12: then 4-7 parts of preheated nano-alumina, 2-5 parts of cobalt nitrate solution, and 1-3 parts of silane coupling agent KH550 are mixed and added into 7-11 parts of sodium silicate solution, and stirred to mix well to obtain nano-alumina liquid; S13: The nano-alumina liquid and the ball milling additive are mixed and stirred in a weight ratio of (5-7):3, and the stirring is completed to obtain a first ball milling liquid; The preparation method of ball milling additive is: 3-5 parts of sodium metaborate and 2-5 parts of montmorillonite are added to 6-8 parts of dopamine hydrochloride solution, and then 1-3 parts of nano-silica sol are added and mixed to obtain a modified immersion solution; The nano-lanthanum oxide powder is immersed in a sufficient amount of the modified immersion liquid and stirred at a stirring speed of 550-650 r / min for 20-30 minutes. After the stirring is completed, the powder is filtered and dried to obtain a ball milling additive. The preparation method of the second ball milling liquid is: S101: preparing a sodium dodecylbenzene sulfonate solution with a mass fraction of 2-5% and a chitosan solution with a mass fraction of 3-6%; S102: 3-5 parts of carbon fiber, 1-3 parts of nano-silicon dioxide, 4-7 parts of sodium dodecylbenzene sulfonate solution and 2-4 parts of chitosan solution are fully mixed to obtain a second ball milling solution.

2. The method for preparing a lithium iron phosphate positive electrode material according to claim 1, characterized in that: The first ball milling treatment is performed at a ball milling speed of 1000-1500 r / min for 35-45 min; The second ball milling treatment is performed at a ball milling speed of 650-750 r / min and the ball milling is performed for 1-2 hours.

3. The method for preparing a lithium iron phosphate positive electrode material according to claim 1, characterized in that: The rotation speed of the blending and stirring process in S13 is 550-650 r / min, and the stirring time is 35-45 min.

4. The method for preparing a lithium iron phosphate positive electrode material according to claim 1, characterized in that: The mass fraction of dopamine hydrochloride solution is 3~5%.

5. The method for preparing a lithium iron phosphate positive electrode material according to claim 1, characterized in that: The speed for sufficient blending is 550~750r / min, and the blending time is 45~55min.

6. A lithium iron phosphate positive electrode material, characterized in that: The lithium iron phosphate positive electrode material is prepared by the preparation method of any one of claims 1 to 5.

Citation Information

Patent Citations

  • A preparation method of an alumina-coated manganese-doped lithium iron phosphate cathode material

    CN109244424A

  • Preparation method of alumina-coated lithium iron phosphate positive electrode material

    CN112614999A